Diachronic trends in the topic distributions of formal epistemology abstracts. - Kinney, David (Synthese, 2022)
Formal epistemology is a growing field of philosophical research. It is also evolving, with the subject matter of formal epistemology papers changing considerably over the past two decades. To quantify the ways in which formal epistemology is changing, I generate a stochastic block topic model of the abstracts of papers classified by as pertaining to formal epistemology. This model identifies fourteen salient topics of formal epistemology abstracts at a first level of abstraction, and four topics at a second level of abstraction. I then study diachronic trends in the degree to which formal epistemology abstracts written in a given year are likely to contain words associated with a particular topic, beginning in 2000 and continuing to 2020. My findings suggest that there has been a marked decline in the likelihood of a given formal epistemology abstract being about logical approaches to belief revision (e.g., AGM belief-revision theory). On the other hand, over the past two decades, the salience of probabilistic techniques in formal epistemology has increased, as has the salience of work at the intersection of formal epistemology and some areas of philosophy of science.